(untitled) (Journal of Computational Mathematics, 1999)
The nonconforming finite element (two Crouzeix-Raviart linear elements and Wilson element) approximations to the unilateral problem are considered. The error bounds for these elements are obtained in the appropriate assumptions of regularity of solution of the problem.